Abstracts of the Twenty-First Annual Academic Sessions, College of Comunity Physicians of Sri Lanka - Upul Senarath; Sumal Nandasena; Thilini Wickramaarachchi; Surangi Jayakody; Dushyanthi Alagiyawanna; Sathira Perera (College of Community Physicians of Sri Lanka, 2017)
Abstracts of the Twenty-First Annual Academic Sessions, College of Comunity Physicians of Sri Lanka, 1-3 September 2016 Contains: List of oral presentations List of poster presentations Abstracts of oral presentations Abstracts of poster presentations Acknowledgements